Monitoring program for assessing population health and clinico-economical effectiveness of regional healthcare system - S. V. Dobrykh; S. V. Alekseeva; O. Yu. Korennova; T. F. Khaysarov (Кардиоваскулярная терапия и профилактика)
The study analysed the information support for healthcare services in Omsk City adult population. The absence of adequate technical and technological means of healthcare information support could explain the low effectiveness of municipal healthcare in reducing disease burden among Omsk City adults. A system for monitoring population health and clinico-economical effectiveness of the regional healthcare services could be developed, based on the technology for processing individual information on Omsk citizens. By early 2009, a computer program “Medinfo-Gorod” was implemented in 27 Omsk polyclinics, which provide healthcare services to 908 006 adults. This system enables doctors to work with electronic medical histories and easily print out standard medical documents. Such a system is an opportunity to create an “electronic passport” of individual health. For healthcare authorities, it provides a source of valid, transparent, and updated information on population health and healthcare effectiveness. Therefore, it facilitates evidence-based decisions in the area of healthcare management, including allocation of financial resources, as well helps to reduce substantial disease burden among adult Omsk population.